A new device to estimate VO2 during incline walking by accelerometry and barometry - Yamazaki, T.; Gen-No, H.; Kamijo, Y.-I.; Okazaki, K.; Masuki, S.; Nose, H. (Medicine & Science in Sports & Exercise, 2009)
Purpose: To examine whether the biased estimation of oxygen consumption rate (VO2, mL/kg·min) by accelerometry during incline walking can be improved by the addition of altitude changes as measured by barometry.